“Me mirabas”: Steven Soderbergh’s Latin America - Ernesto R. Acevedo-Muñoz (Mise au Point)
Steven Soderbergh’s Latin American-themed films, Traffic and Che, display differences in setting and topics based on formal and cinematography practices that emphasize visual distinctions as markers of otherness. In these films Soderbergh explores political, social, linguistic and personal conflicts through the use of distinct filters, lenses, camera set-ups, aspect ratios, and language. The visual design in Traffic seems to suggest the Mexico setting as “other” or “marginal” and the US sequences as central. This essay, however, explores the ways in which the “look” of Latin America -Mexico in Traffic, Cuba and Bolivia in Che- shifts perceivably between the two films making the representation of the US -specifically Cincinnati, Washington DC, and New York City- look “strange” or “unnatural”. Formal elements such as mise-en-scène, cinematography, and speech appear to be revised over the course of the films, consistent with a shift of focus and sympathy towards the Latin American “other."